PENGARUH TANGGUNGJAWAB PELAKSANAAN FUNGSI BISNIS DAN FUNGSI SOSIAL TERHADAP JUMLAH DANA PIHAK KETIGA BANK UMUM SYARIAH DI INDONESIA (Periode Tahun 2010-2015) - Nafisah Ruhana; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study aims to find out the simultaneous and partial impact of Good Corporate Governance index and Islamic social reporting index as an assessment of the responsibility for the implementation of business functions and social functions towards total third–party funds on Islamic Banks in Indonesia during 2010-2015. This study use quantitative approach, and the sampling technique is purposive sampling. The analysis technique used is the panel data regression. The type and sources of data used are secondary data. The population in this study are Islamic Banks in Indonesia.The results of this study showed that index of good corporate governance partially have no significant effect on the number of third-party funds while index of Islamic Social Reporting partially have significant effect on the amount of funding third parties. Simultaneously index of Good Corporate Governance and Islamic Social Reporting have significant effect on the number of third-party funds Islamic banks.  REFERENCESAl-Qur’an dan Terjemahannya.Ajija, Sochrul D, Dyah W.Sari, Rahmat H.Setianto, dan Martha R. Primanti. 2011. Cara Cerdas Menguasai Eviews. Jakarta. Salemba Empat.Al Qurthubi, Syaikh Imam. 2009. Tafsir Al Qurthubi. Jakarta: Pustaka AzzamAnshori, Muslich & Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press Antonio, Muhammad Syafi’i. 2001. Bank Syari’ah Dari Teori Ke Praktek, Jakarta: Gema Insani.Boone, Louis E. & David L. Kurtz. 2002. Pengantar Bisnis Jilid 1. Jakarta: ErlanggaBrigham, Eugene F. & Joel F. Houston. . Manajemen Keuangan. Jilid 1. Edisi 8. Terjemahan oleh Dodo Suharto dan Herman Wibowo. 2001. Jakarta: Erlangga.Dendawijaya, Lukman. 2003. Manajemen perbankan. Ghalia IndonesiaDepartemen Agama RI. 2011. Al-Qur’an Tajwid & Terjemah. Bandung: CV Penerbit DiponegoroEmirzon, Joni. 2006. Regulatory Driven dalam Implementasi Prinsip-prinsip Good Corporate Governance pada Perusahaan di Indonesia. Jurnal Manajemen dan Bisnis Sriwijaya Vol.4 No.8 Desember. PalembangGujarati, Demodar N dan Dwan C. Porter. 2013. Dasar-Dasar Ekonometrika. Edisi 5 Buku 2. Jakarta: Salemba EmpatGumanti, Tatang A. 2009. Teori Sinyal dalam Manajemeng Keuangan. Majalah Usahawan Lembaga Management FEUI No.06 TH XXXVIII.Haniffa, Ros. 2002. Social Reporting Disclosure: An Islamic Perspective. Indonesian Management & Accounting Research Vol 1, No 2 pp 128-146.Indriantoro, Nur & Bambang Supomo. 2011. Metodologi Penelitian Bisnis Untuk Akuntansi dan Manajemen. Edisi 1. Yogyakarta: BPFEIsmail. 2011. Perbankan Syariah. Jakarta: Kencana.Jensen, Michael C. & William H. Meckling. 1976. Theory of The Firm: Managerial Behaviour, Agency Cost and Ownership Structure. Journal of Financial Economics 3, (Online), (http://www.sciencedirect.com/science/article/pii/0304405X7690026X, diakses 11 Mei 2016). 305-360.Kasmir. 2006. Manajemen perbankan. Jakarta: Raja Grafindo PersadaKatsir, Ibnu. 2005. Tafsir Ibnu Katsir. Jilid 8. Bogor. Pustaka Imam Syafi’i.Keraf, Sonny. 1998. Etika Bisnis Tuntutan dan Relevansinya, Yogyakarta: KanisiusKNKG. 2006. Pedoman Umum Good Corporate Governance Indonesia. Jakarta: Komite Nasional Kebijakan GovernanceMahaputra, Adindha. 2011. Mekanisme Tata Kelola Perusahaan yang Baik dan Luas Pengungkapan Pelaporan Tanggung Jawab Sosial pada Perusahaan yang Masuk Corporate Governance Perception Index. Skripsi Universitas AirlanggaNurhayati, Sri dan Wasilah. 2009. Akuntansi Syariah di Indonesia. Jakarta: Salemba empatOthman, et al. 2009. Determinants of Islamic Social Reporting Among Top Shariah-Approved Companies in Bursa Malaysia. Research Journal of Internatıonal Studıes - Issue 12 (October, 2009)Othman, Rohana dan Azlan Md Thani. 2010. Islamic Social Reporting of Listed Companies in Malaysia. International Business & Economics Research Journal – April 2010. Volume 9, Number 4Peraturan Bank Indonesia Nomor 11/ 33/ PBI/2009 Tentang Pelaksanaan Good Corporate Governance bagi Bank Umum Syariah dan Unit Usaha SyariahPeraturan Otoritas Jasa Keuangan No. 8/POJK.03/2014 tentang Penilaian Tingkat Kesehatan Bank Umum Syariah dan Unit Usaha SyariahSebagai Variabel Intervening. Jurnal Ekonomi Kuantitatif Terapan Vol. 7 No. 1 ISSN: 2301-8968.Rivai, Veithzal. 2010. Islamic Banking: Sistem Bank Islam Bukan Hanya Solusi Menghadapi Krisis Namun Solusi Dalam Menghadapi Berbagai Persoalan Perbankan & Ekonomi Global: Sebuah Teori, Konsep, dan Aplikasi. Jakarta: Bumi Aksara.Sulistyanto, H.Sri. 2003. Good Corporate Governance: Bisakah Meningkatkan Kepercayaan Masyarakat?. Jurnal Ekonomi dan Bisnis –EKOBIS, Vol.4/No.1/Januari 2003. Fakultas Ekonomi Universitas Islam Sultan Agung Semarang.Sulistyanto, H.Sri. 2008. Manajemen Laba Teori dan Model Empiris. Jakarta: GrasindoSurat Edaran Bank Indonesia No. 12/13/DPbSSurat Edaran Otoritas Jasa Keuangan No. 10/SEOJK.03/2014Sutedi, Adrian. 2011. Good Corporate Governance. Jakarta: Sinar GrafikaUndang-Undang Republik Indonesia Nomor 10 tahun 1998 tentang perbankanUndang-Undang Republik Indonesia Nomor 21 tahun 2008 tentang perbankan syariahWibisono, Yusuf. 2007. Membedah Konsep & Aplikasi CSR. Gresik: Fascho Publishing